Significant perceived stressors in irritable bowel syndrome: a stress interventional module analysed - Gupta, Sanjay; Singh, Nitesh Kumar; Verma, Vinod (International Journal of Research in Medical Sciences, 2020)
Background: Psychological stress is an important factor for the development of irritable bowel syndrome (IBS). More and more clinical and experimental evidences are showing that IBS is a combination of irritable bowel and irritable brain. As IBS is a stress sensitive disorder, its treatment should focus on managing stress and stress-induced responses. Methods: This is a hospital based longitudinal study. 72 patients fulfilling the Rome IV criteria for irritable bowel syndrome were enrolled into the study. Perceived stress was assessed using student stress dimension questionnaire (SSDQ) while IBS severity was assessed using IBS severity scoring system (IBS-SSS). The stress interventional module (SIM) consist of specific domain targeted psychological interventions given to the patients weekly based on the stress domain mapping. The effectiveness of these interventions on reducing stress as well as IBS severity was assessed at baseline, and weeks 2, 4 and 6 follow-ups. Results: Of the studied IBS patients, most had SPS in multiple life domains while familial and interpersonal domains were affected in 78%. Also, total stress load in form of mean cumulative stress load at baseline was 451.1 which decreased significantly to 274.4 over 6 weeks. This SIM brought about a reduction in mean irritable bowel syndrome severity score from 27.5 to 20.6 in 6 weeks. This reduction in IBS severity score overtime was significant (p=0.001). Conclusions: Patients of irritable bowel syndrome show significant stress in multiple domains of life, which require proper assessment and management. Authors propose that individual-specific interventions aimed at reducing stress in all psychosocial life domains are efficacious and should be an integral part of managing IBS.